The Authoritarian Nationalism, the Rejection of Liberalism and the Use of Binary Oppositions in Bolivia. A Critique of the Conservative Character of Progressive Intellectuals - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The main points of Bolivia’s political culture arise from colonial times. They have suffered of course many alterations; the most important one has been caused by the modernization process in the second half of the 20th century. But the leading features of that culture are still alive: authoritarianism, paternalism and centralism, on the one side, and the slow, inefficient, and complicated functioning of the state bureaucracy, on the other. This problem, which preserves antidemocratic regimes, was not recognizes as such by Bolivia’s most important Marxist, René Zavaleta Mercado.